A tangled web: Comparing inter‐ and intraspecific mating dynamics in Anasa squash bugs. (17th December 2021) - Greenway, E. V(Ginny); Hamel, Jennifer A.; Miller, Christine W.
Abstract: Reproductive interference, reproductive interactions between heterospecific individuals including mating, is commonly reported across taxa, but its drivers are still unclear. Studying interspecific matings in the context of their conspecific mating system—by relating an individual's conspecific mating behaviour to its heterospecific interactions—offers a powerful approach to address this uncertainty. Here, we compare inter‐ and intraspecific mating dynamics in the squash bug Anasa tristis and its close relative Anasa andresii under semi‐natural conditions. Using replicated enclosures, we surveyed the mating behaviour of individually marked A .  tristis and A .  andresii (five males and five females of each species per trial) at hourly intervals using a robotic camera system over a 14‐day period. We uncovered high levels of reproductive interference (19% of individuals engaged in interspecific matings), but the majority of mating activity took place between conspecifics. A .  tristis females which engaged in interspecific matings had comparable hatching success with those which did not. Therefore, in this system, relatively high levels of reproductive interference may emerge under semi‐natural conditions as a by‐product of limited intraspecific pre‐copulatory choice paired with limited fitness penalties for at least one of the species involved. Abstract : Reproductive interference (RI), costly reproductive interactions between individuals of different species, is a common yet little understood behaviour. In this study, we compare inter‐ and intraspecific mating dynamics in the squash bug Anasa tristis to better understand drivers of interspecific mating interactions. We uncovered high levels of reproductive interference (19% of individuals engaged in interspecific matings), but the majority of mating activity took place between conspecifics. Female Anasa tristis were also highly polyandrous, and we found those which engaged in occasional interspecific matings had comparable hatching success to those which did not. In this system, at least, relatively high levels of reproductive interference likely emerged as a by‐product of relaxed intraspecific pre‐copulatory choice, paired with limited fitness penalties in our focal species.